Design and test of a wheel-belt type cotton stalk puller - Cai, Jialin; Zhang, Jiaxi; Gao, Zebin; Wang, Xiaoxuan; Guo, Gang; Baikeli, Yasenjiang; Tang, Xuepeng; Wang, Yichao (International Journal of Agricultural and Biological Engineering, 2024)
During the harvesting process, rigid materials are prone to causing damage to the cotton stalks, which will increasethe risk of stalk breakage. A cotton stalk pulling component that blends stiff and flexible materials was devised to lower thebreaking rate. The cotton stalk pulling component was made up of rollers and flexible belts that pull the stalks using clampingforce and the forward speed of the tractor. The influence of various factors in the equipment on the harvesting effect of cottonstalks were analyzed through response surface experiments, and a multiple quadratic regression response surface model withmissing pulling rate and breakage rate as response values was established. The significant of influencing factors on the breakingrate of cotton stalks are in a descending order as: the angle of cotton stalk pulling, tractor’s forward speed, and the clampingspeed of the cotton stalk component. The working parameters of the wheel-belt type cotton stalk pulling machine have beenoptimized using the response surface combination experimental method, and the optimal parameter combination was obtainedas: tractor forward speed of 4.5 km/h, cotton stalk pulling angle of 60°, and clamping speed of the cotton stalk pullingcomponent of 349 r/min. The results of validation experiments showed that the missing pulling rate of cotton stalks was 5.06%and the breakage rate was 13.12%, indicating a good harvesting effect of the cotton stalks. The model was reasonable and theperformance parameters could meet the relevant inspection requirements. The results can provide a reference for furtherresearch on the technology of flexible cotton stalk pulling. Keywords: cotton stalk puller, wheeled belt, flexible cotton stalks pulling, verification testing DOI: 10.25165/j.ijabe.20241702.7287 Citation: Cai J L, Zhang J X, Gao Z B, Wang X X, Guo G, Yasenjiang Baikeli, et al. Design and test of a wheel-belt type cottonstalk puller. Int J Agric & Biol Eng, 2024; 17(2): 102–108.